Biochemical and technological characterization of two C4 gluten‐free cereals: Sorghum bicolor and Eragrostis tef. Issue 1 (6th October 2019) - Galassi, Elena; Taddei, Federica; Ciccoritti, Roberto; Nocente, Francesca; Gazza, Laura
Abstract: Background and objectives: Most commonly used gluten‐free cereals, as rice and corn, are reputed to be inferior in their nutritional value, particularly regarding dietary fiber and proteins content. The use of minor cereals has been limited also because of their reduced technological and sensory properties. The aim of this study was to evaluate five food‐grade sorghum hybrids and three teff genotypes (brown and white grain), for their technological, biochemical, and nutritional characteristics, and to test their suitability for the formulation of innovative wholegrain, gluten‐free products of high nutritional value. Findings: Both sorghum and teff revealed a protein and total dietary fiber content of 9%–12% (w/w), and good technological properties. Conclusions: The present study indicated that these niche cereals manifest their technological and nutritional potential, also in Italian pedo‐climatic conditions, constituting promising raw materials for enhancing the diversification in nutrition, contributing to the development of healthier foods and sustainable agriculture. Significance and novelty: Sorghum and teff could meet the need of gluten‐intolerants and health‐conscious consumers and encourage the use of niche crops also in Western Countries.